Controlling the transcription levels of argGH redistributed l-arginine metabolic flux in N-acetylglutamate kinase and ArgR-deregulated Corynebacterium crenatum. (1st January 2016) - Zhao, Qinqin; Luo, Yuchang; Dou, Wenfang; Zhang, Xian; Zhang, Xiaomei; Zhang, Weiwei; Xu, Meijuan; Geng, Yan; Rao, Zhiming; Xu, Zhenghong
Abstract: Corynebacterium crenatum SYPA5-5, an l -arginine high-producer obtained through multiple mutation-screening steps, had been deregulated by the repression of ArgR that inhibits l -arginine biosynthesis at genetic level. Further study indicated that feedback inhibition of SYPA5-5  N -acetylglutamate kinase (CcNAGK) by l -arginine, as another rate-limiting step, could be deregulated by introducing point mutations. Here, we introduced two of the positive mutations (H268N or R209A) of CcNAGK into the chromosome of SYPA5-5, however, resulting in accumulation of large amounts of the intermediates (l -citrulline and l -ornithine) and decreased production of l -arginine. Genetic and enzymatic levels analysis involved in l -arginine biosynthetic pathway of recombinants SYPA5-5-NAGKH268N (H-7) and SYPA5-5-NAGKR209A (R-8) showed that the transcription levels of argGH decreased accompanied with the reduction of argininosuccinate synthase and argininosuccinase activities, respectively, which led to the metabolic obstacle from l -citrulline to l -arginine. Co-expression of argGH with exogenous plasmid in H-7 and R-8 removed this bottleneck and increased l -arginine productivity remarkably. Compared with SYPA5-5, fermentation period of H-7/pDXW-10- argGH (H-7-GH) reduced to 16 h; meanwhile, the l -arginine productivity improved about 63.6 %. Fed-batch fermentation of H-7-GH in 10 L bioreactor produced 389.9 mM l -arginine with the productivity of 5.42 mM h −1 . These results indicated that controlling the transcription of argGH was a key factor for regulating the metabolic flux toward l -arginine biosynthesis after deregulating the repression of ArgR and feedback inhibition of CcNAGK, and therefore functioned as another regulatory mode for l -arginine production. Thus, deregulating all these three regulatory modes was a powerful strategy to construct l -arginine high-producing C. crenatum .